Coastal habitat conservation using community education as a tool : a case study in Mukim Tanjung Kupang, Johor / Serina Abdul Rahman - Abdul Rahman, Serina (Institute of Graduate Studies, UiTM, 2014)
Mukim Tg Kupang and its adjacent coastal habitats harbour a rich variety of seagrass meadows, mangroves and rocky shores which are home to myriad endangered species and other cryptic fauna. However this area is slated for development and the local fishing community who depend on it needs to be equipped with the ability to cope with inevitable urbanisation and change. This case study proposed a longterm science-based environmental education program aimed at a primary audience of local children and youth (aged 6-18, n=34) that would disseminate conservation knowledge and encourage environmentally-friendly behaviour and a conservation mindset to the wider community. After two years of the education program, another year on-site focussed on developing community empowerment through an extended initiative that roped in older youth (aged19-28) and local women, and this proved to be the key success factor in the study.